Gypsum and green manuring influence soil sodicity and mustard productivity under semi-arid conditions of Rajasthan - Saraswat, Pankaj Kumar; Chaudhary, Banshidhar; Rathore, S.S.; Bhati, Ashu Singh (Annals of Agricultural Research, 2016)
Three on farm-testing (OFTs) on green manuring for introduction and assessment of their effects on mustard production and sodic soil quality were conducted at farmer’s field during 2011-12 to 2013- 14 in selected villages of Niwai and Todaraisingh Tehsil of Tonk district. OFT treatments comprised as T1 : farmer’s practice-FP, T2 Gypsum 50% GR + RDF + Green gram, T4 GR + RDF + Crotolaria as technological interventions. Results of OFT’s revealed that technological interventions T4 whereas T3 (Gypsum 50% GR + RDF + Green gram) could registered significantly higher yield only over T1 . Higher monitory gains in terms of benefit cost ratio (B:C ratio) were also achieved in T4 treatments. Inclusion of green manuring (GM) particularly Sesbania and Crotolaria along with T5 Gypsum use resulted in to remarkable reduction in pH, EC and BD and improvements in organic carbon, available NPK and micronutrients in sodic soils in Tonk district of Rajasthan. Introduction of green manuring in kharif fallow fields reserved for mustard sowing in rabi season got fitted in prevailing cropping system. : Recommended POP for mustard (Gypsum 50% GR + FYM+ RDF), T3 : : Gypsum 50% GR + RDF + Sesbania and T5 : Gypsum 50% and T5 registered significantly higher mustard yield even over FP and POP treatments and